IMPLEMENTASI MANAJEMEN PEMBIAYAAN (Di MTs Miftahul Jannah Nagreg Kabupaten Bandung) - Mulyana, Nanang (Jurnal Pelita Nusa, 2021)
ABSTRACT This study aims to determine the implementation of financial management in Madrasah Tsanawiyah, as well as related to supporting and inhibiting factors in Madrasah Tsanawiyah, especially in Madrasah Tsanawiyah Miftahul Jannah Nagreg Kab. Bandung. The existence of this research originated from the importance of financing and finance in Islamic education institutions because financing is one of the supporting components and is important for activities in the education process at Madrasah. The type of research in this research uses field research and includes descriptive qualitative research, this research is through data sources from information and documents, data collection techniques are through interviews, documentation, and observation, and using data analysis techniques, namely data reduction, data presentation, and then withdrawal. conclusion. The results of this study indicate that the financing management carried out at MTs Miftahul Jannah Nagrek Kab. Bandung, namely: (1) the financing system at Madrasah Tsanawiyah Miftahul Jannah refers to the Indonesian Government Regulation on Education Funding and national education standards (SNP) PP RI No. 19 of 2005 in article 62. (2) In addition, the funding for education that runs at MTs Miftahul Jannah uses the full cost of the School Operational Assistance (BOS) funds, and there is no collection of any funds to students/parents of students so that all students are 100% free. (3) The supporting factors include supporting infrastructure and human resources according to standards. (4) The obstacle is the small amount of budget input obtained by MTs Miftahul Jannah Nagreg Kab. Bandung. Keywords: Management, Financing, Madrasah.